PERAN DINAS PERDAGANGAN DAN PERINDUSTRIAN KOTA PEKANBARU DALAM PENGEMBANGAN PASAR BAWAH SEBAGAI OBJEK WISATA BELANJA DI PEKANBARU - Citra Alivania Adri; Musadad " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Shopping is one of the activities that can be used as a tourist attraction. One object that is used as an icon for shopping tourism in Pekanbaru City is Pasar Bawah. The purpose of this study is to find out what the role of the Pekanbaru City Trade and Industry Office is as a motivator, facilitator and dynamist as well as the obstacles experienced in market development efforts.This study uses qualitative methods with data collection techniques in the form of observation, interviews, and documentation. The results of this study indicate that as a motivator, the agency has indirectly provided encouragement and also an opportunity to improve skills for traders. As a facilitator, the agency only contributes to the provision of land, as well as the construction of roads around the market. As a dynamist, the service routinely provides guidance with managers, but the service does not provide guidance or provide training to traders who are the front line who will directly deal with Pasar Bawah visitors. The biggest obstacle experienced by the department in developing Pasar Bawah as a shopping tourism object in Pekanbaru City is the problem of budget costs. Keywords: The role of the department of trade and industry, development, tourism, shopping, pasar